PENERAPAN METODE SOBEL UNTUK PENGUKURAN TINGGI BADAN MENGGUNAKAN WEBCAM - Putra, Ade Noversi; Basukesti, Agus; Nugraheny, Dwi (Compiler, 2013)
Measurement o f human height is usually done with the help o f others. But with the Sobel method, measurement o f human height can be done alone. It can simplify the process o f measuring human height. The method is a development method robert sobel using filter HPF (high pass filter) that given a zero buffer. This method takes the principle o f the laplacian and gaussian function is known as a function to generate HPF. Applications designed using sobel method can be used for high meassure an object with a small error rate. Best distance o f 20 cm from the background to the object seen from the results o f the error rate.